Evaluating the impact of AsmaDroid® on knowledge, attitude, and behavior of relapse prevention among asthmatic patients - Ghozali, Muhammad Thesa; Ikawati, Zullies; Lazuardi, Lutfan (Intelektual Pustaka Media Utama, 2024)
The success of asthma self-management is determined by three essential factors: healthcare professionals, patients, and drugs. Regarding patient factors, the level of knowledge plays a role and leads to a positive attitude and behavior to prevent future attack relapse. This quasi-experimental study aimed to determine the effectiveness of a mobile phone app-assisted educational intervention in improving the quality of knowledge, attitude, and behavior among patients with asthma. The study included 140 participants who were divided into two groups, i.e., control and treatment. The treatment group received and installed the app into their smartphone and then was asked to study all the educational materials in the app for four weeks. A test was carried out before and after the intervention period to examine the effectiveness of the intervention. This study used the statistical program IBM® SPSS® Version 22.0 to analyze data, and a parametric statistical test was utilized to test the statistical hypothesis in this investigation. The study found improvement, as many as 87.14% for knowledge, 77.14% for attitude, and 67.15% for behavior, with a p-value each of 0.01. It could be concluded that digital-based patient education using a mobile app improves the patients' knowledge, attitude, and behavior.